An embedded computer-based texting and GPS sharing gadget for android smartphone - Nurzarina Omar Sharif, 1993- , author; Shamsudin Mohd. Amin, supervisor; Fakulti Kejuruteraan Elektrik (2016)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2016